(untitled) (Bangladesh Journal of Child Health, 2017)
Approximately 9 of 1000 live births have congenital heart disease, of these 25% have critical congenital heart disease (CCHD). Delayed or missed diagnosis of CCHD may result in acute cardiovascular collapse. Echocardiography is a necessary diagnostic tool but its cost is a severe limitation as a universal screening tool. Clinically undetectable hypoxemia is present to some degree in most CCHD and this technique can be used as a screening method for early detection. In 2012, a systematic review involving over 300,000 babies reported that pulse oximetry test is highly specific (99.9%) and moderately sensitive (76.5%) with a low false positive rate (0.05%). The test is simple, feasible, cost effective, highly specific and sufficiently sensitive to qualify for screening test. Parents and caregivers should be informed that pulse oximetry cannot detect all cases of CCHD. A positive test result needs to be confirmed by echocardiography, which is considered as the definitive diagnostic modality. Whenever possible, the echocardiogram should be interpreted by pediatric cardiologists Bangladesh J Child Health 2015; VOL 39 (3) :148-153